Neutrophil depletion in the pre-implantation phase impairs pregnancy index, placenta and fetus development - Hebeda, Cristina Bichels; Savioli, Anna Carolina; Scharf, Pablo; de Paula-Silva, Marina; Gil, Cristiane Damas; Farsky, Sandra Helena Poliselli; Sandri, Silvana (Frontiers in Immunology, 2022)
Maternal neutrophils cells are players in gestational tolerance and fetus delivery. Nonetheless, their actions in each phase of the pregnancy are unknown. We here investigated the role of maternal neutrophil depletion before the blastocyst implantation phase and outcomes in the pregnancy index, placenta, and fetus development. Neutrophils were pharmacologically depleted by i.p. injection of anti-Gr1 (anti-neutrophils; 200 µg) 24 hours after plug visualization in allogeneic-mated C57BL/6/BALB/c mice. Depletion of peripheral neutrophils lasted until 48 hours after anti-Gr1 injection (gestational day 1.5-3.5). On gestational day 5.5, neutrophil depletion impaired the blastocyst implantation, as 50% of pregnant mice presented reduced implantation sites. On gestational day 18.5, neutrophil depletion reduced the pregnancy rate and index, altered the placenta disposition in the uterine horns, and modified the structure of the placenta, detected by reduced junctional zone, associated with decreased numbers of giant trophoblast cells, spongiotrophoblast. Reduced number of placenta cells labeled for vascular endothelial growth factor (VEGF), platelet-endothelial cell adhesion molecule (PECAM-1), and intercellular cell adhesion molecule (ICAM-1), important markers of angiogenesis and adhesiveness, were detected in neutrophil depleted mice. Furthermore, neutrophil depletion promoted a higher frequency of monocytes, natural killers, and T regulatory cells, and lower frequency of cytotoxic T cells in the blood, and abnormal development of offspring. Associated data obtained herein highlight the pivotal role of neutrophils actions in the early stages of pregnancy, and address further investigations on the imbricating signaling evoked by neutrophils in the trophoblastic interaction with uterine epithelium.